Financial education in the teaching-learning process of high school students at the French Lycée of San Salvador (Educational Knowledge, 2021)
This study analyzed the financial literacy knowledge of first- and second-year high school students at the French Lycée of San Salvador during 2020. This involved identifying the students' understanding of saving, responsible consumption, and investment practices. An exploratory-descriptive study was conducted to gain an understanding of the financial literacy of the students at this institution.The research was carried out with 116 students of both sexes, aged 14 to 18. The survey technique was used, with a questionnaire as the instrument. Teachers of subjects related to financial education were also interviewed to gather information on its presence in their curricula.The results showed that students possess knowledge about saving: putting money aside for future needs or consumption, among other reasons. However, opinions were divided regarding the students' responsible consumption practices. Furthermore, the students expressed that they knew what investing means and its risks, but not about the types of investment.
Keywords: Financial Education; saving; consume responsibly; investment